How Women Can Improve Their Venture Pitch Outcomes - Malmström, Malin; Malmström, Malin; Wesemann, Henrik; Wincent, Joakim (MIT Sloan Management Review, 2020)
A large-scale study in Europe of funding decisions finds that VCs evaluate male and female entrepreneurs by different standards. Savvy entrepreneurs can anticipate potentially biased responses to their pitches and plan accordingly. Certain tactics keep audiences engaged and confident of the idea's potential, positioning the petitioner to succeed.